2018
DOI: 10.31788/rjc.2018.1122068
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Total Phenolic Content, Total Flavonoid Content, and Antimutagenic Activity of Ethanol Extract Nanoparticles of Rhaphidophora Pinnata (L.F) Schott Leaves

Abstract: Phenolic and flavonoid compounds in plants are a natural source of antioxidants which can inhibit the development of several types of diseases in humans, such as cardiovascular diseases and cancer. This study aimed to determine total phenolic content, total flavonoid content, and antimutagenic activity of ethanol extract nanoparticles of Rhaphidophora pinnata (L.f) Schott leaves. The total phenolic content and the total flavonoid content of Rhaphidophora pinnata extract was determined with Folin-Ciocalteu meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Secondary metabolites in the methanol extract of non-geothermal leaves are not flavonoids. Flavonoid compounds in plants are a natural source of antioxidants that can inhibit the development of several types of diseases in humans, such as cardiovascular diseases and cancer 17 . Laban leaves contain flavonoids, saponins, tannins, triterpenoids/steroids, and glycosides 6 .…”
Section: Organoleptic Testmentioning
confidence: 99%
“…Secondary metabolites in the methanol extract of non-geothermal leaves are not flavonoids. Flavonoid compounds in plants are a natural source of antioxidants that can inhibit the development of several types of diseases in humans, such as cardiovascular diseases and cancer 17 . Laban leaves contain flavonoids, saponins, tannins, triterpenoids/steroids, and glycosides 6 .…”
Section: Organoleptic Testmentioning
confidence: 99%
“…The data were expressed as Mean ± SEM and analyzed using one-way ANOVA followed by post hoc Tukey to find the different variables [8]. Differences were considered as statistically significant at p < 0.05 when compared with control.…”
Section: R Pinnata Leaves Were Obtained Frommentioning
confidence: 99%
“…The previous research showed that the leaf performs cytotoxicity activity with brine shrimp test method and MTT assays. R. pinnata also possess antioxidant activity with 1,1-diphenyl-2-pikrihidrazil, which is an active anticancer toward cell MCF-7 and is a antimutagenic [7], [8]. The previous study showed that R. pinnata had the potential to be an anti-cancer and hence possess the anti-inflammatory and analgetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…9 The products which are developed from the natural plants are a good source of new antimicrobials owes to low toxicity cause minimal environmental pollution and have a low risk of development of resistance by pathogenic microorganism. 10 Some plants possess antimutagenic activity due to the presence of its total phenol and flavonoid content 11 and certain aquatic plant-like watercress contains a promising level of pharmaceutical and nutritional sources. 12 Fig.…”
Section: Introductionmentioning
confidence: 99%